Medical Care Costs Were Similar Across the Low-dose Computed Tomography and Chest X-Ray Arms of the National Lung Screening Trial Despite Different Rates of Significant Incidental Findings. Issue 5 (May 2018) - Gareen, Ilana F.; Black, William C.; Tosteson, Tor D.; Wang, Qianfei; Sicks, JoRean D.; Tosteson, Anna N.A.
Abstract : Background: The National Lung Screening Trial (NLST) reported lung cancer and all-cause mortality reductions for low-dose computed tomography (LDCT) versus chest x-ray (CXR) screening. Although LDCT lung screening has received a grade B from the United States Preventive Services Task Force and is a covered service under most health plans, concerns remain on the costs engendered by screening, and the impact of the high rate of significant incidental finding (SIF) detection on those costs. Methods: We linked American College of Radiology Imaging Network NLST and Medicare fee-for-service claims data for participants from 23 sites for 2002–2009. We performed participant-level analyses using generalized linear regression models to estimate the adjusted annual mean of the 3-year total medical costs per person in each study arm and within screen outcome categories (ever positive with abnormalities suspicious for lung cancer, always negative for abnormalities suspicious for lung cancer, but with SIFs, and always negative without SIFs). Results: The adjusted annual mean total per person costs were not significantly different between screening arms [LDCT, $11, 029 (95% confidence interval, $10, 107–$11, 951); CXR, $10, 905 (95% confidence interval, $10, 059–$11, 751)], despite higher proportions of individuals with SIFs in the LDCT versus the CXR arm (18% vs. 4%; P <0.0001). Conclusions: We found little difference in total annual per person costs between LDCT-screened and CXR-screened Medicare participants, despite the higher number of SIFs in the LDCT arm of the study. Abstract : Supplemental Digital Content is available in the text.